Design Of Generator Test Equipment With Microcontroller-Based Dummy Load Heating Element With Fuzzy Logic Method - Tohir, Toto; Baisrum, Baisrum; Putra, Pahreza Ridwan; ilman, sofyan muhammad; Putra, Febi Ariefka Septian; Habinuddin, Endang (Bandung State Polytechnic (Politeknik Negeri Bandung), 2023)
New power plants are urgently needed to support the needs of the community and industry in accordance with government regulations on the need for renewable energy sources. However, in its implementation, the construction of this new power plant is hampered by the absence of facilities and infrastructure, especially the technology that supports it, one of which is pre-operation activities. At this stage, it is necessary to test the generators that will be used in the plants. Generators are an important component in the electricity system. Meanwhile, research on generator testing is still rare, as are the tools that support the process of generator testing. This study aims to design a generator test tool so that this test can take place more effectively and efficiently. In general, the testing method uses a dummy load so that the load on the generator can be manipulated. With fuzzy logic control on dummy load control, the testing process can be done more optimally and can be monitored on a larger system. The results of this study showed current measurement with a maximum error of 1.64%, voltage measurement with a maximum error of 0.5%, frequency measurement with a maximum error of 0.4%, and a maximum control error of 5.7%. The automation system applied is still limited to monitoring electrical parameters.